The President's Authority in Granting Abolition as State Mercy From A Legal and Political Perspective (Case Study of Tom Lembong's Abolition) - Rizky Nanda Rifa'i; Dani Muhtada (Law Research Review Quarterly, 2026)
This study examines the authority of the President in granting abolition within the framework of the Indonesian rule of law, focusing on the tension between legal certainty and substantive justice. The main issue of this study is the shift in the function of abolition from a normative corrective mechanism to a pragmatic political instrument, as seen in the controversial case of Thomas Trikasih Lembong. The purpose of this study is to analyze the philosophical and juridical basis of abolition and to evaluate how political dynamics influence the decision to grant abolition in 2025. Using a normative legal research method through a legislative, conceptual, and case approach, this study finds that although abolition has a constitutional basis in Article 14 section (2) of the 1945 Constitution of the Republic of Indonesia, its implementation in the Thomas Lembong case functions as "political language" to maintain national stability and reconciliation among elites. The findings of the study show a gap between formal legal legitimacy and public perception, where abolition is viewed ambivalently as a means of reconciliation and a potential source of impunity for elites. This study concludes that abolition is an important "safety valve" in the constitutional system to bridge procedural law with humanitarian values, but transparent technical regulations and objective criteria are needed to ensure that this discretionary authority remains accountable and consistent with the principles of justice and the rule of law.